(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This study develops and evaluates an improved methodology for enhancing teachers’ professional competence in the context of higher education internationalization. As universities in Uzbekistan increasingly engage in international partnerships, joint programs, and English-medium instruction, faculty members face mounting pressure to transform their professional practice beyond traditional pedagogical approaches. A quasi-experimental design was employed with 96 faculty members from two universities: an experimental group (n=48) receiving a 16-week Integrated Professional Development Program (IPDP) comprising intercultural competence training, technology-enhanced pedagogy workshops, collaborative teaching practicums, and reflective portfolio development, and a control group (n=48) following conventional professional development activities. Pre- and post-intervention assessments measured four competence dimensions: pedagogical innovation, intercultural communication, digital literacy, and reflective practice. Results demonstrated statistically significant improvements in the experimental group across all dimensions, with the largest effect observed in intercultural communication (t(94) = 5.83, p < 0.001, d = 1.19) and pedagogical innovation (t(94) = 4.97, p < 0.001, d = 1.02). Qualitative data from reflective portfolios and focus groups revealed that collaborative international teaching experiences and structured reflection were perceived as the most transformative components. These findings provide an empirically validated framework for faculty professional development in internationalizing higher education institutions.